Análise de bacilos gram negativos em superfícies inanimadas de uma unidade de terapia intensiva neonatal - Marques, Lara de Andrade (2019)
Introduction: Hospital surfaces may be contaminated by Gram-negative bacteria, acting as a reservoir for these pathogens. Objectives: To determine the presence of Gram-negative bacteria isolated from the hospital surfaces of a Neonatal Intensive Care Unit by analyzing resistance profile, Extended Spectrum β-Lactamases (ESBL) and AmpC production, as well as check for infections and colonizations caused by these microorganisms. Methods: Environmental samples were collected with sterile swab moistened with 0.9% saline also sterilized. Gram-negative bacteria were identified by MALDI-TOF MS. Antimicrobial Susceptibility Testing was performed and all micro-organisms were screened for ESBL and AmpC production. Results: Of the 408 samples collected, 30 were positive for Gram-negative bacteria, 19 were Multidrug Resistant, 10 were ESBL and 19 AmpC producers. Daily surveillance included 148 neonates admitted to the NICU during the study period, 38 had infections isolating 56 samples obtained from different sites, 17 of them producing ESBL and 25 of AmpC. Conclusion: Gram-negative bacteria were found to contaminate the environment, including multidrug resistant ESBL and AmpC-producing samples, posing a risk to NICU neonates.